So You're a Program Committee Member Now: On Excellence in Reviews and Meta-Reviews and Championing Submitted Work That Has Merit - Hinckley, Ken (MobileHCI, 2015)
This document discusses what goes into being a great reviewer, meta-reviewer, and all-around champion for the papers entrusted to you as a program committee member. Although written with the MobileHCI conference in mind— a “smaller venue” focused on mobility rather than a large “flagship conference” like CHI—much of the discussion applies to program committee work, reviewing, and even authoring more persuasive papers in general. It also touches on some of the responsibilities, pitfalls, and true joys of ushering a paper into the scientific canon of HumanComputer Interaction. Excellence in program committee work requires a certain attitude: an ability and desire and by-golly stubborn willingness to make yourself see hidden gems, and new facets of contribution, in papers that occasionally have rough edges—yet valid and important contributions to offer the field nonetheless. You must embrace the belief that the chief responsibility of a program committee member is to accept papers, and not to find flaws and reject work at every opportunity.